Pengaruh Pajak Hotel, Pajak Restoran, Dan Pajak Hiburan Terhadap Peningkatan Pendapatan Asli Daerah Kota Medan - Muhammad Rafli Hudhawi Nasution; Muhammad Ikhsan Harahap (Pusat Riset dan Inovasi Nasional, 2024)
The research aims to determine whether or not there is an influence of hotel tax and entertainment tax on increasing local revenue in the city of Medan. This type of research is descriptive quantitative, with data collection techniques using observation and interviews. The results of research conducted at the Medan City BPPRD show that hotel taxes and entertainment taxes have increased but there are still some that have not reached the target. The variables used are hotel tax and entertainment tax as independent variables and local revenue as the dependent variable to determine the effect of hotel tax on increasing local revenue in the city of Medan. The partial research results show that hotel taxes have a significant effect on regional origin. Restaurant tax has a significant effect on local revenue. Entertainment tax has a significant effect on local revenue.